Edukasi Pencegahan dan Pengelolaan Hipertensi Pada Pralansia dan Lansia di Desa Padang Mancang - Sufyan Anwar; zakiyuddin zakiyuddin; Yarmaliza Yarmaliza; Siti Maisyaroh Fitri Siregar; Dian Fera (COMSEP: Jurnal Pengabdian Kepada Masyarakat, 2021)
Hypertension is a major public health problem, especially in an aging population. However, there are still some middle age and elderly people who have unhealthy lifestyles, such as smoking, lack of physical activity and unhealthy diets. This condition may be related to the lack of knowledge about hypertension. This program was carried out using the 60-minute lecture and discussion method involving 17 participants (middle age and elderly) in Padang Mancang Village, Kaway XVI sub-district, West Aceh district in 2018. The results of providing education show that there is an increase in participant knowledge, where more participants can answer questions about hypertension that were asked after giving the material / lecture. The existence of correct knowledge about hypertension can have an impact on efforts to prevent and control hypertension that can be carried out by middle age and elderly through a healthy lifestyle.